Role of the microflora in distal intestinal tract by maintaining oxalate homeostasis - Osolodchenko, T; Lukyanenko, T; Andreieva, I; Volyanskiy , D; Shtiker , L; Kosubova , H (Annals of Mechnikov's Institute, 2020)
Human intestinal microflora is part of the human body and performs numerous function. Considerable research interest is in the field of probiotics for the prevention of kidney stones, which is one of the most common urological diseases.Urolithiasis is one of the most common urological diseases. This is polyetiological disease congenital and acquired character with complex physical and chemical processes that occur not only in the urinary system, but also the whole body. None of the treatments does not guarantee full recovery of the patient and often leads to relapse. The open methods of removal stones yield news minimally invasive the technologys. Development of stone formation depends on the presence of many factors, metabolic disorders, chronic urinary tract infections, genetic disorders and more. Most have the following metabolic disorders as hypercalciuria, hiperurikuria, hipotsytraturia , hyperoxaluria and hipomahniuria. Among all types of urolithiasis kaltsiyoksalatnyy ranked first in the prevalence rate - about 75.0 - 85.0 % of cases. Dietary restriction by oxalates іs the unreliable method of preventing disease. Although there is evidence for the growth inhibition normobiocenosis representatives, which in turn enhances the absorption of salts of oxalic acid oxalate in the application of sodium , magnesium and cobalt in their intragastric administration. Recently published many papers on the impact on the level of oxalate intestinal microflora. The first publications appeared on the influence of gram-negative obligate anaerobes O. formigenes the concentration of oxalate in the urine. This anaerobic bacteria living in the colon, its prevalence - 46.0 % - 77.0 % of the adult population. O. formigenes reveals the symbiotic interaction with the human body by reducing absorption of oxalate in the intestinal cavity with subsequent decrease in their concentration in plasma and urine. O. formigenes has two key enzymes - oksalyl - koadecarboxylase and formyl - koatransferase performing metabolic conversion of oxalate in the cavity of the colon.The polymerase chain reaction has advantages over previously adopted methods - culture and photometric in the diagnosis of the presence of O. formigenes. The taking of antibiotics reduces of O. formigenes in the colon. The microorganism is resistant to amoxicillin, ceftriaxone, vancomycin and is sensitive to ciprofloxacin, clarithromycin, azitromitsyn, clindamycin, doxycycline, gentamicin levofloxacin, tetracycline and metranidazol. In the metabolism of oxalate involved and other microorganisms. There are studies that prove the value of other taxonomic groups oxalate degradation: E. coli, Lactobacillus spp. There is the concept that the use of probiotics is capable of degradation of oxalate in the gut and reducing their absorption in the gastrointestinal tract. There is investigated microbiological method for the treatment of urolithiasis and hyperoxaluria through the use of probiotic O. formigenes (at the stage of clinical trials). This method is not traumatic, it can be efficient, cost-effective and environmentally safe. Implicitly that Lactobacillus spp. and E. coli, along with O. formigenes, are promising targets for further research and their application in the field of biotechnological production. To improve the efficiency and expanding the range of their application further work in search and development of new probiotics , given the requirements for food and pharmaceuticals that will effectively dostato prevent or reduce the number of recurrent stone formation.